Novel Isoprene-Degrading Proteobacteria From Soil and Leaves Identified by Cultivation and Metagenomics Analysis of Stable Isotope Probing Experiments - Larke-Mejía, Nasmille L.; Crombie, Andrew T.; Pratscher, Jennifer; McGenity, Terry J.; Murrell, J. Colin (Frontiers in Microbiology, 2019)
Isoprene is a climate-active gas and one of the most abundant biogenic volatile organic compounds (BVOC) released into the atmosphere. In the terrestrial environment, plants are the primary producers of isoprene releasing between 500-750 million tonnes per year to protect themselves from environmental stresses such as direct radiation, heat and reactive oxygen species. While many studies have explored isoprene production, relatively little is known about consumption of isoprene by microbes and the most well-characterized isoprene degrader is a Rhodococcus strain isolated from freshwater sediment. In order to identify a wider range of bacterial isoprene-degraders in the environment, DNA stable isotope probing (DNA-SIP) with 13C-labelled isoprene was used to identify active isoprene degraders associated with soil in the vicinity of a willow tree. Retrieval by PCR of 16S rRNA genes from the 13C-labelled DNA revealed an active isoprene-degrading bacterial community dominated by Proteobacteria, together with a minor portion of Actinobacteria, mainly of the genus Rhodococcus. Metagenome sequencing of 13C-labelled DNA from SIP experiments enabled analysis of genes encoding key enzymes of isoprene metabolism from novel isoprene degraders. Informed by these DNA-SIP experiments and working with soil from the vicinity of tree species known to produce high amounts of isoprene, four novel isoprene-degrading strains of the genera Nocardioides, Ramlibacter, Variovorax and Sphingopyxis, along with strains of Rhodococcus and Gordonia, genera that are known to contain isoprene-degrading strains, were isolated. The use of lower concentrations of isoprene during enrichment experiments has revealed active Gram-negative isoprene-degrading bacteria associated with isoprene-emitting trees. Analysis of isoprene-degradation genes from these new isolates provided a more robust phylogenetic framework for analysis of isoA, encoding the alpha- subunit of the isoprene monooxygenase, a key metabolic marker gene for cultivation-independent studies on isoprene degradation in the terrestrial environment.